Development of leadless packaged heavily doped N-type 4H-SiC pressure sensor family for harsh environments - Lukang Wang; Nuo Wan; Yu Yang; Yabing Wang; You Zhao; Jiaoyang Zhu; Minye Yang; Yi Lyu; Ming Liu; Yulong Zhao (Microsystems & Nanoengineering)
Abstract In many industries, there is a growing demand for semiconductor pressure sensors capable of operating in harsh environments with extremely high and low temperatures and high vibrations. Utilizing the piezoresistive effect of heavily doped N-type 4H-SiC, we proposed a family design of eight pressure sensor chip structures featuring different diaphragm shapes of circles and squares, along with different piezoresistor configurations. The 4H-SiC piezoresistive pressure sensor was developed using micro-electromechanical systems (MEMS) technology and encapsulated in a leadless package structure via low-stress connection achieved by glass frit sintering. The 4H-SiC pressure sensor demonstrates impressive performance, exhibiting an accuracy of 0.18% FSO and a temperature tolerance range from −50 to 600 °C, with a temperature coefficient of zero output as low as 0.08%/°C at 600 °C. Furthermore, the developed sensor shows remarkable stability under conditions of high-temperature vibration coupling. The advancement of this family of 4H-SiC pressure sensors provides a promising solution for pressure measurement in harsh industrial environments.